COMPARISON OF LONG-TERM ASSETS RECORDKEEPING IN COMPLIANCE WITH THE LEGISLATIONS OF THE EU AND SLOVAKIA - Nora Štangová; Agneša Víghová (European Scientific Journal, ESJ, 2014)
The need to own assets, whether in the form of long-term tangible or intangible assets, conditions a successful operation of an accounting entity in some cases. The objective of the article is to compare the asset structure defined for public sector accounting entities to the asset structure binding for business entities in compliance with the legislation valid in SR. Further objective of the article is to compare the legislation valid in SR in terms of long-term assets to the legislation defined under IAS/IFRS International Accounting Standards (applicable for businesses) and IPSAS (applicable for public sector entities). Our effort is to point out the differences on the grounds of the given comparisons, and to propose measures aimed at enhancing the legislation on the grounds of the analysis.